Muslim and Catholic experiences of national belonging in France: rethinking boundaries, inequities, and faith in the republic - Ferrara, Carol (Islam of the global West, 2024)
"Through a comparative ethnographic analysis of divergent French Muslim and Catholic experiences of (non)belonging and civic engagement, this book offers new insights into the consequences of majoritarian national identity upon the lives of variously positioned pious citizens. Drawing upon 15 months of ethnographic fieldwork in Paris, Lille, and Lyon, France within spaces of religious education and interfaith dialogue, the book illustrates the constraints that Muslims face as compared to their more privileged Catholic co-citizens"--